Effectiveness of Group Schema Therapy on Life Attitude and Distress Tolerance in Women Attending Counseling Clinics - Forouzani , Safoura; Norbakhsh Amiri, Fatemeh; Abbasi , Mahdieh; Pilehvar Zavareh , Somayeh; Maghsoudi , Shirin (Psychology of Woman Journal, 2023)
Objective: The aim of the present study was to determine the effectiveness of schema therapy on life attitude and distress tolerance in women attending counseling clinics. Methods and Materials: The research method was a quasi-experimental design with pre-test and post-test along with a control group. The study population consisted of women attending counseling clinics in Tehran in 2023. The sampling method was convenience sampling, and the sample size was selected to be 30 individuals (15 in the experimental group and 15 in the control group). Data collection was carried out using life attitude and distress tolerance questionnaires. The experimental group underwent eight 90-minute schema therapy sessions, while the control group did not receive any intervention. Both groups completed the life attitude and distress tolerance questionnaires in two phases: pre-test and post-test. Findings: Findings indicated that after schema therapy, with attention to the mean variables of life attitude and distress tolerance, the experimental group showed significant improvement in the post-test compared to the mean of the control group. Conclusion: Therefore, schema therapy has an effect on the life attitude and distress tolerance of women attending counseling clinics.